Low thermal conductivity and high figure of merit for rapidly synthesized n-type Pb1−xBixTe alloys. Issue 44 (31st October 2018) - Chen, Tingting; Wang, Hongchao; Su, Wenbin; Mehmood, Fahad; Wang, Teng; Zhai, Jinze; Wang, Xue; Wang, Chunlei
Abstract : High zT s of Pb1− x Bi x Te alloys rapidly synthesized at low temperature in this study are comparable to those from conventional melting synthesis. Abstract : High figures of merit of n-type Pb1− x Bi x Te alloys have been achieved by rapid synthesis at low temperature. The effects of Bi dopant and microwave hydrothermal technology on microstructure and thermoelectric performance have been studied. The solid solubility limit of Bi in PbTe is between x = 0.02 and 0.03. Homogenous nanopowders of about 70 nm have been synthesized by the microwave hydrothermal method. When followed by hot pressing, sub-microscale grain sizes are also formed for Pb1− x Bi x Te alloys. With increase in Bi, the carrier concentration is improved within the solubility limit. This leads to low electrical resistivity and higher power factor at high temperature. A higher power factor of 8.5 μW cm −1 K −2 is obtained for x = 0.02 sample at 623 K. In addition, the introduction of Bi effectively prohibits the p–n transition and bipolar thermal conductivity of pristine PbTe. Thus, a low lattice thermal conductivity of 0.68 W m −1 K −1 is achieved at 673 K, combining scattering of alloys, grain boundaries, dislocations and defects. As a result, the highest peak figure of merit, i.e., zT = 0.62 at 673 K is achieved for Pb0.98 Bi0.02 Te sample, which is comparable with that of Bi-doped PbTe alloys synthesized by the conventional melting method. Thus, the right synthesis conditions of the microwave hydrothermal method can rapidly result in thermoelectric materials with comparable figures of merit.